PENGARUH RASIO KEUANGAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN TELEKOMUNIKASI - Sekar Mayang Sari; Setyaningsih Sri Utami; Dorothea Ririn Indriastuti (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2021)
The purpose of this study was to analyze the effect of liquidity ratios, leverage, and profitability on financial distress in telecommunications companies listed on the Indonesia Stock Exchange in 2013-2019. The population in this study were 6 companies listed on the Indonesia Stock Exchange in 2013-2019. Sampling with saturated sampling method and obtained 6 samples. Collecting data using documentation techniques through the Indonesia Stock Exchange website. The analysis technique used is the classical assumption test, multiple linear regression analysis, t test, F test, and the coefficient of determination. The results showed that simultaneously and partially the ratio of liquidity, leverage, and profitability had a simultaneous effect on financial distress.